- Analisis Trend Riset Pekerja Sosial (Social Worker) Anak dan Lanjut Usia: Analisis Trend Riset Pekerja Sosial (Social Worker) Anak dan Lanjut Usia - Dewanti, Nafansyah; Ana, Ana; Widiaty, Isma (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2025)
This research background is stem from the issue that social worker faced in this globalization era. In this modern era, social worker is playing a vital role in supporting individual and group in-need such child and elderly care in their work. To fully support is role in society, a social worker must know the challenges it faced, especially in child and elderly social work, but there is a scarcity in research to understand social worker issue faced. The research trend analysis in child and elderly social work needed to understand the need that the social worker must prepared in the future. The purposes of this research is to analyse the trend to shows the challenge social worker faces in the child and elderly social worker in the field, both in national level and international level. This research uses analytical approach on 30 accredited national and international research journal on child and elderly care. This research result shows the topic that becoming a trend on child and elderly care research journal in 2020-2023 such as child exploitation, child abuse, child with disability, child trouble with law, child education,technology on child care support, elderly health, neglected elderly, elderly skill training, and the development on elderly support care. The trend shows that the trend research in child care is dominant than the others, which is child abuses and child education. In other note, trend on elderly care show that elderly health support and technological advancement in elderly support being a dominant research trend on elderly care research journal. This show a lack of research on social work theme, especially on child and elderly social work. As such, this research recommend that a further research on trend in child and elderly care research is necessary to better understand the issue that social worker faced in the modern era. Key Words : Social Worker, Child social work, Elderly Social work, Research trend